Financial mainstreaming for the rural poor: The JEEViKA experience - Choudhury, Mahua Roy (Technical Centre for Agricultural and Rural Cooperation, 2018)
In the state of Bihar, India, the mobilisation of rural women into community self-help groups has emerged as an effective means of linking the poorest members of society with the formal banking system. The results seen in a relatively short time have been impressive.